A case-control study of oral contraceptive use and breast cancer. - Hennekens, C; Speizer, F; Lipnick, R; Rosner, B; Bain, C; Belanger, C; Stampfer, M; Willett, W; Peto, R (1984)
Among 989 cases of breast cancer and 9,890 controls selected from a cohort of married, female registered nurses aged 30-55 years, the relative risk (RR) of breast cancer for women who had ever used oral contraceptives (OC) compared with those who had never used them was 1.0, with 95% confidence limits 0.9-1.2. Among OC users, there was no consistent pattern of excess risk with increasing duration; in fact, the few women who had used OC longest (greater than 10 yr) had a slightly lower risk than never-users. Moreover, there was no association between OC use and breast cancer among women with a positive history of breast cancer in the mother or sister or with OC use before their first pregnancy. The only subgroup of women among whom any adverse effect was apparent was current OC users aged 50-55 years (two onsets expected vs. seven observed). This finding is consistent with earlier reports of an increased risk of breast cancer among older OC users; however, it is also likely to reflect, at least to some extent, the play of chance, since at ages 45-49 and in each younger age group fewer cases than expected were observed among current OC users.